2014
DOI: 10.1002/2013jc009754
|View full text |Cite
|
Sign up to set email alerts
|

Potential drivers of sinking particle's size spectra and vertical flux of particulate organic carbon (POC): Turbulence, phytoplankton, and zooplankton

Abstract: Phytoplankton spring blooms in temperate and high-latitude shelf seas are commonly associated with an enhanced particulate organic carbon (POC) export of aggregates from the euphotic zone. In contrast, a postbloom situation is usually linked to a predominant POC retention, where small cells (<10 lm) and strong grazing pressure prevail. This study aimed to examine impacts of turbulence, phytoplankton, bloom stage, and zooplankton abundance on the sinking particles' size spectra and POC flux to improve the under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 88 publications
(123 reference statements)
1
19
0
Order By: Relevance
“…Additionally, deep vertical mixing in the area of the Polar Front enhances the export of high-quantity and high-quality particulate organic carbon (POC), thus favoring tight pelagic−benthic coupling (Olli et al 2002, Reigstad et al 2008. Wiedmann et al (2014) emphasized the role of mixing and turbulence for POC export to deeper areas: they showed that export of POC can be high in post-bloom situations, given that vertical mixing occurs. Tamelander et al (2006) analyzed the pelagic−benthic coupling in the Barents Sea MIZ during summer and detected tight coupling between surface production and the benthic community over relatively small scales.…”
Section: Drivers Of Megabenthic Secondary Productionmentioning
confidence: 99%
“…Additionally, deep vertical mixing in the area of the Polar Front enhances the export of high-quantity and high-quality particulate organic carbon (POC), thus favoring tight pelagic−benthic coupling (Olli et al 2002, Reigstad et al 2008. Wiedmann et al (2014) emphasized the role of mixing and turbulence for POC export to deeper areas: they showed that export of POC can be high in post-bloom situations, given that vertical mixing occurs. Tamelander et al (2006) analyzed the pelagic−benthic coupling in the Barents Sea MIZ during summer and detected tight coupling between surface production and the benthic community over relatively small scales.…”
Section: Drivers Of Megabenthic Secondary Productionmentioning
confidence: 99%
“…The composition of sinking particles can affect both the magnitude and efficiency of carbon flux from the surface ocean through the mesopelagic zone and into the deep ocean (Boyd and Newton 1999;Wilson et al 2008;Wiedmann et al 2014). Detrital material often composes the largest fraction of sinking particulate organic carbon (POC) (Fowler and Knauer 1986;Guidi et al 2008b).…”
mentioning
confidence: 99%
“…Detrital material often composes the largest fraction of sinking particulate organic carbon (POC) (Fowler and Knauer 1986;Guidi et al 2008b). Several studies have identified changes in the abundance and composition of large fecal pellets and organic aggregates by examining particles individually (Ebersbach and Trull 2008;Guidi et al 2008a;Wiedmann et al 2014), and have linked these observations to changes in the magnitude and efficiency (i.e., attenuation with depth) of carbon flux (Wilson et al 2008;Wiedmann et al 2014). Depending on the study location and season, either aggregates or fecal pellets can be responsible for similar proportions of carbon flux (Waite and Nodder 2001;Ebersbach and Trull 2008), suggesting that particle identification is important to determine the particular ecological mechanism that drives carbon flux at specific locations and times.…”
mentioning
confidence: 99%
“…2). Betaine and DMSP are both osmolytes, which are molecules present in the cytosol of cells that regulate osmotic pressure as well as assist in maintaining protein structure (Yancey et al 1982).. Betaine, by far the largest contributor to the metabolite composition of the sinking particles, is an osmolyte utilized by organisms across the domains of life, although it is less commonly used in phytoplankton than DMSP (Yancey et al 1982;Boch et al 1997;Keller et al 1999;Lai and Lai 2011). Betaine concentrations can reach 170 mM inside a phytoplankton cell (Keller et al 1999), suggesting that this metabolite is likely to be measured at relatively high concentrations in particulate samples.…”
Section: Fluctuations Of Osmolytes On Sinking Particlesmentioning
confidence: 99%
“…For instance, while rapidly sinking phytoplankton cells during blooms are generally considered to contribute to a large export flux of organic carbon, fecal pellets produced by grazing can contribute similar or greater total fluxes of organic matter out of the euphotic zone (Wiedmann et al 2014). These different sources may affect the molecular composition of the sinking particles with implications for the metabolic pathways expressed by the microbial community during organic matter degradation.…”
Section: Introductionmentioning
confidence: 99%